Orthodox Clergy and Right-Wing Political Movements in Russia at the Beginning of XX Century: Church Press - A. A. Ivanov (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The question of the attitude of the Orthodox Russian clergy to the right-wing political parties at the beginning of the 20th century — the Black Hundreds (the Union of the Russian People, the Russian People’s Union named after Mikhail Archangel, etc.) and Russian nationalists (the All-Russian National Union and related organizations) is considered. The novelty of the research is seen in the introduction into scientific circulation of new sources (materials of the church press), which make it possible to make a number of significant clarifications in the existing ideas about the relationship between the Orthodox Church and right-wing political organizations. Particular attention is paid to the differences in the views of clergymen on the Black Hundred unions and political structures of Russian nationalists. The reasons for the cooperation of conservative Orthodox pastors with the Black Hundred unions and organizations of Russian nationalists and the circumstances that forced the clergy to show concern for the views and activities of right-wing parties are shown. It is argued that the secularization and Westernization of Russian nationalism, which led to the departure of its ideologists and followers from the foundations of the Orthodox doctrine and church worldview, became the main reasons for the wary attitude of church circles towards the political organizations of Russian nationalists.